(3GdQbGHI GdHQdeGfjI Ydi CYeGd GdMcheI (B:s (3OQGSI ebGQfI (B/ s - (3fhGa egOj LhjQ GdMeOhfjs; (3CfhQ CMeO QSdGfs; (3LGeYI GdOhd GdYQHjIs (3eYgO GdHMhK hGdOQGSGJ GdYQHjIs ((3GdbGgQI(B:s (3bSe GdHMhK hGdOQGSGJ GdYQHjI (B- (3LGeYI GdOhd GdYQHjI,s, 2009)
(3ai YGde Gdjhe dG jefcf JUhQ OhdI JOYi HGfgG OjebQGWjI JMJQe GdMQjGJ hJUhf GdMbhb HOhf hLhO HQdeGf efJNH ajgG ggeG cGf Tcdg Ch JSejJg hegeG cGf Tcd fXGe GdMce ai gPg GdOhdI, ajbhe gPG GdHQdeGf HGdJYHjQ Yf CQGA GdTYH heYJbOGJg ef CLd JMbjb CgOGag hZGjGJg (B.s
(3QSGFd fSNI efaQOIs
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdOhd GdYQHjI, eYgO GdHMhK hGdOQGSGJ GdYQHjI, bSe GdHMhK hGdOQGSGJ GdbGfhfjI, (B2009.s
(3jTJed Ydi EQLGYGJ HjHdjhLQGajI(B: 174-187(3UaMIs
Keywords: (3GdbGfhf GdOSJhQjs; (3GdJMbjb GdHQdeGfj s; (3dLGf GdJMbjb GdHQdeGfjs; (3WdH GdefGbTI GdYGeIs; (3GdGbJQGM HQZHIs; (3GdGSJLhGH GdHQdeGfjs; (3GdSdWI GdJTQjYjIs; (3GdSdWI GdJfajPjIs; (3GdSdWI GdbVGFjIs; (3QSGFd LGeYjIs -- (3LGeYI GdOhd GdYQHjIs